Crafting the future of rice in Indonesia: sustainable supply through systems thinking - Wiwit Widyawati; Nuhfil Hanani AR; Syafrial Syafrial; Sujarwo Sujarwo (Cogent Social Sciences)
Climate change’s impact on agriculture has been observed in several studies, and combined with the issue of decreasing rice harvest areas, it has the possibility of reducing the success of rice production in Indonesia. This is likely to significantly impact Indonesia’s rice supply and threaten national food security. This study aims to explain the dynamics of Indonesian rice availability in terms of production, consumption, and trade by identifying key variables influencing supply. This study utilizes a systems thinking approach with Vensim software for model development. Applying the basic system pattern—an interpretive tool that captures the complex behavior of rice supply—shows that rice availability in Indonesia is determined by domestic production, which is influenced by harvest area, seed varieties, fertilizers, climate, irrigation, and pests and diseases. In addition to domestic production, Indonesia imports rice from Asian countries. Retail rice prices, as well as the prices of alternative foodstuffs such as sago, potatoes, and other similar commodities, all influence rice demand. This study provides a more nuanced understanding of the underlying factors influencing rice supply system behavior. As a result, policymakers can better address the underlying causes of Indonesia’s rice demand and supply imbalance.